Formação profissional, científica e tecnológica para professores não licenciados: saberes, conhecimentos e competências docentes - Machado, Adriano Silveira (2023)
This study investigated, at the same time, the effectiveness, described and interpreted processes of a training process for teachers who do not have a degree in pedagogical areas, and who teach in Basic Education, in Secondary Education in professional schools in the State of Ceará, in order to find ways and pedagogical practices that reveal knowledge, knowledge and skills more favorable to the professional training of teachers. The problem of the investigation sought to study the distance training process of professionals considering the training urgency of teachers. Its objective is to identify whether the training provided, with its procedures and planned actions, favors or not the construction of a pedagogical praxis based on intervention and teaching work, in the course of a training process in Professional, Scientific and Technological Education (EPCT). The research was characterized as a case study centered on the Improvement in Teaching course in Professional Education at the Basic and Technical Levels. In the research, a set of studied documents was gathered, consisting of: textualized reports in discussion forums, intervention projects, reports, case reports, reports of pedagogical interventions, course conclusion works and interviews. Thematic categorical content analysis was carried out in all collected documents, given that the use of this methodology is in line with the objective, with the investigative problem, with the data collection procedures, and made it possible for them to become perceptible and measurable for the researcher, to put an end to them, to make them susceptible to inferences, and to obtain answers to research questions. The study of the problem makes it possible to point out the effectiveness and impact of this type of training on professional development, to find ways and pedagogical practices that reveal conducts, strategies and pedagogical knowledge favorable to professional teacher training